The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/j.1460-2075.1988.tb02947.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of human papillomavirus transcription in non-tumorigenic cells by 5-azacytidine.

Abstract: The transcription of human papillomavirus type 18 (HPV 18) is selectively suppressed in non‐tumorigenic HeLa x fibroblast or HeLa x keratinocyte cell hybrids by 5‐azacytidine. In contrast, viral gene expression is not influenced by 5‐azacytidine in both tumorigenic hybrid segregants and in the parental HeLa cells. The suppression mechanism seems to operate at the level of initiation of transcription since nuclear run‐on experiments show the absence of elongated nascent viral RNA, whereas the transcription of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…To check RNA quality, 5 g of RNA was separated on 1% agarose gels in the presence of ethidium bromide under non-denaturing conditions (36). For RT 1-3 g of RNA was mixed with 0.2 g of random primers (Roche), heated at 70°C for 10 min, and chilled on ice.…”
Section: Rna Analysis and Reverse Transcriptase (Rt)-pcr-cytoplasmicmentioning
confidence: 99%
See 1 more Smart Citation
“…To check RNA quality, 5 g of RNA was separated on 1% agarose gels in the presence of ethidium bromide under non-denaturing conditions (36). For RT 1-3 g of RNA was mixed with 0.2 g of random primers (Roche), heated at 70°C for 10 min, and chilled on ice.…”
Section: Rna Analysis and Reverse Transcriptase (Rt)-pcr-cytoplasmicmentioning
confidence: 99%
“…This allows the examination of AP-1 in a cellular environment harboring identical viral transcription cassettes (36), but where the oncoproteins are expressed in a different genetic background (35). As depicted in Fig.…”
Section: Inverse Correlation Of C-fos and Fra-1 Expression In Tumorigmentioning
confidence: 99%
“…For instance, hepatic differentiation can be induced by 5-AzaC in rat fetuses (Rothrock et al, 19881, and fetal hemoglobin expression can be induced by this drug in adult baboons (Constantoulakis et al, 1989). The effects of 5-AzaC have also been demonstrated with studies of many other genes in various cell types, including marrow stromal cells (Andrews et al, 19891, HL-60 cells (Kong et al, 1991), fibroblasts (Chiang, 19811, and many transformed cells (Robert et al, 1988;Rosl et al, 1988;Avedimento et al, 1989;Rimoldi et al, 1991). More direct evidence has come from sequencing of a particular genomic DNA fragment (Church and Gilbert, 1984;Slauz et al, 1986).…”
mentioning
confidence: 90%
“…Moreover, inhibition of DNA methylation and histone deacetylation has been shown to promote keratinocyte differentiation (Rosl et al, 1988;Schmidt et al, 1989;Staiano-Coico et al, 1989), and an inverse correlation between DNA methylation and the expression of differentiating genes has been demonstrated in human keratinocytes (Engelkamp et al, 1993;Elder and Zhao, 2002). It has also been suggested that inhibition of differentiation by AEA occurs through changes in chromatin methylation patterns (Paradisi et al, 2008;Pasquariello et al, 2009), and that AEA induces DNA methylation of keratinocyte-differentiating genes by increasing DNA methyltransferase (DNMT) activity via a CB 1-dependent involvement of p38 and p42/p44 MAPK (Paradisi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%